Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1161/01.res.59.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Phasic blood flow velocity pattern in epimyocardial microvessels in the beating canine left ventricle.

Abstract: We quantitated phasic epimyocardial microcirculatory coronary blood flow velocity patterns in the beating left ventricle. Using a newly developed floating objective and high-speed cinematography, red cell velocities in small arterioles, capillaries, and small venules and microvascular diameters in the superficial layer of the epimyocardium of beating left ventricle were determined throughout the entire cardiac cycle in open-chest anesthetized dogs. Heart rate was maintained at 140 beats/min by means of left at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…[22][23][24] Previous reports from our laboratory have demonstrated that the reactivity of observed vessels to various vasoactive substances or to physiological stimuli is well preserved in this preparation. 11,18,20,25,26 In the present study, the vasodilation of arterial microvessels was also clearly demonstrated when the perfusion pressure was reduced, indicating that the reactivity of the observed vessels was well preserved. The diameters of coronary arterial microvessels at the baseline and at perfusion pressures of 60 mmHg (mild stenosis) and 40 mmHg (severe stenosis).…”
Section: Critique Of Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…[22][23][24] Previous reports from our laboratory have demonstrated that the reactivity of observed vessels to various vasoactive substances or to physiological stimuli is well preserved in this preparation. 11,18,20,25,26 In the present study, the vasodilation of arterial microvessels was also clearly demonstrated when the perfusion pressure was reduced, indicating that the reactivity of the observed vessels was well preserved. The diameters of coronary arterial microvessels at the baseline and at perfusion pressures of 60 mmHg (mild stenosis) and 40 mmHg (severe stenosis).…”
Section: Critique Of Methodssupporting
confidence: 71%
“…[18][19][20] Briefly, a floating objective consists of a pair of convex lenses aligned on a common optical axis, and this apparatus transmits the real image of the epimyocardium of the beating heart to a fixed position without any change in magnification. The convex lens facing the heart can move in unison with the cardiac motion without touching the cardiac surface.…”
Section: Microscope Systemmentioning
confidence: 99%
“…3,13 With this system, the surface of the beating heart can be continuously observed throughout the cardiac cycle. An objective lifter was used to carefully adjust the distance between the objective and microvessels, so as not to compress the detector microvessel.…”
Section: Bioassay Methodsmentioning
confidence: 99%
“…4,5,13,14 Briefly, the dogs were anesthetized and ventilated. A thoracotomy was performed, and the pericardium was cut to expose the heart surface.…”
Section: Beating-heart Preparationmentioning
confidence: 99%
“…Although the cardioprotec-tive property of MLB has been studied extensively, as well as those of S miltiorrhiza depside salts, there is still no report concerning their effect on coronary microcirculation. To our knowledge, we demonstrated here for the first time that S miltiorrhiza depside salts could improve myocardial microperfusion using laser Doppler flowmetry, as well as CO. A number of strategies have been previously employed to optimize the laser Doppler system to overcome movement artifacts so that it can be used for myocardial microvascular measurement [13][14][15][16][17][18][19] . In the present study, we proposed that the probe was satisfactorily positioned when a distinct and regular waveform pattern was observed during baseline measurements and was altered following intervention, as suggested by Klassen et al [15] .…”
Section: Discussionmentioning
confidence: 99%